Biogeochemical and phospholipid-derived fatty acid (PLFA) composition of deep-water hexactinellid and demosponges from New Zealand collected during SONNE cruise SO254 - Tanja Stratmann; Kathrin Busch; Anna de Kluijver; Michelle Kelly; Sadie Mills; Sven Rossel; Peter Schupp (PANGAEA, 2024)
During R/V Sonne cruise SO254 around New Zealand (January-February 2017), deep-sea sponges were incubated in-situ and ex-situ to measure oxygen consumption, inorganic nutrient fluxes, bacterial and phospholipid-derived fatty acid (PLFA) composition. The biogeochemical composition of 4 shallow-water and deep-water sponge species were determined after the cruise by measuring the organic and total carbon and nitrogen content of freeze-dried sponge tissue and the stable isotopic composition (δ13C, δ15N) of the tissue. Phospholipid-derived fatty acids (PLFAs) of freeze-dried sponge tissue were extracted using a modified Bligh-Dyer extraction protocol and subsequently the PLFA concentrations were measured using gas chromatography flame ionization detection (GC-FID).